In Silico Analysis of Secondary Metabolites of Clerodendrum inerme as a Potential Antidiabetes Compounds - Hilmy, Fauzan; Jamil, Ahmad Shobrun; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2472, 2023)
Clerodendrum inerme can potentially alleviate diabetes, but little is known about its molecular mechanisms. This study aimed to investigate the chemical compound of C. inerme and its molecular mechanism to treat diabetes. The KNApSAcK was used to find secondary metabolite of C. inerme . A screening was done to find compounds by estimating Absorption, Distribution, Metabolism, and Excretion (ADME) on the SwissADME. The SwissTargetPrediction tool connects predictions of target proteins from compounds that pass screening to various probable proteins and utilizing the StringDB to show the network between target proteins and associated diseases. After finding the target protein, continue docking the chemical compound to the target protein using PyRx with AutoDock 4.2.6. The result from StringDB found four chemical compounds ((Z)-3-Hexenyl beta-D-glucopyranoside, Rhodioloside, Sammangaoside B, Clerodermic acid) that can connected to 4 target proteins (DPP4, IL1B, PPARA, PPARG). According to the docking results, clerodermic acid has good protein binding properties with DPP4, IL1B, PPARA, PPARG, rammangaoside B with PPARG, and rhodioloside with DPP4. C. inerme contains clerodermic acid, rammangaoside B, and rhodioloside compounds, which can potentially treat diabetes mellitus.